Observations on the life cycle of the symbiont-bearing foraminifer Amphistegina lobifera Larsen, An invisive species in coastal ecosystems of the Aegean Sea (Greece, E. Mediterranean) - Triantaphyllou, M.; Dimiza, M.; Koukousioura, O.; Hallock, P. (Journal of Foraminiferal Research, 2012)
Members of the family Amphisteginidae have been nearly ubiquitous contributors to shelf carbonate facies through most of the Cenozoic. The most prolific carbonate producer of modern representatives is Amphistegina lobifera Larsen, which is the largest and shallowest dwelling of the Indo- Pacific taxa. This epiphytic, symbiont-bearing foraminifer is also a remarkably successful invasive species in coastal ecosystems of the eastern Mediterranean, where its shell production is altering the composition of shoreline sediment. This paper reports a temporal study of an A. lobifera population collected monthly between June 2008–May 2009 in the Vravron/Attica coastal ecosystem of the south Evoikos Gulf (Aegean Sea), where winter temperatures can drop below previously reported minima for the species. Monthly variations in size, frequency distribution, and abundance indicate that this population reproduced primarily during the summer (July–September), when both asexual and sexual reproduction occurred simultaneously, suggesting a predominantly coeval, one-year life span for each generation. However, a modest increase in juveniles in January indicates some winter reproduction. Comparison of these findings with previous studies shows that a) tolerance of low winter temperatures, b) adaptation of the life cycle to strong seasonality, and c) the mixotrophic feeding strategy have allowed A. lobifera to proliferate in the exceptionally clear, low nutrient, coastal waters of the Mediterranean Sea. These attributes elucidate how previous Cenozoic populations of Amphistegina were able to rapidly expand their latitudinal ranges and invade shallow epeiric seas during episodes of climatic warming.